SEOR2 in Arabidopsis mediates Ca2+ dependent defense against phytoplasmas and reduction of plant growth - Keziah Omenge; Ottone Carmelo Viscardo; Fernando Rodrigo De Oliveira Cantao; Simonetta Santi; Aart Jan Eeuwe van Bel; Rita Musetti (Scientific Reports)
Abstract The Arabidopsis seor1ko line, which expresses the protein AtSEOR2 free of its bond with AtSEOR1, exhibits a lower phytoplasma titre as compared to wild type plants. In search for mechanism(s) underlying potential SEOR2-mediated defense responses the transcriptome of healthy wild type and Atseor1ko plants was disclosed by RNA sequencing. Comparative transcriptome analysis revealed 1036 differentially expressed genes (DEGs, 893 up- and 143 down-regulated) between the Atseor1ko line and the wild type. Sequence annotation and classification of the up-regulated genes identified “plant-pathogen interaction” among the most enriched clusters. The “plant-pathogen interaction” cluster included genes encoding members of the protein kinase superfamily, actors in calcium/calmodulin signaling transduction and WRKY transcription factors. An interaction network analysis and a host-phytoplasma interaction map demonstrated that AtSEOR2 protein could interact with the calcium-binding proteins CAM2 and TCH3. The latter one also turned out to be an indirect target of the SAP54CY phytoplasma effector, which suggests a SEOR2-mediated role of TCH3 in balancing nutrient investments in plant defense and plant growth.